Associations between implant alignment or position and patient-reported outcomes after total hip arthroplasty. (July 2022) - Shoji, Takeshi; Inoue, Tadashi; Kato, Yuichi; Fujiwara, Yusuke; Sumii, Junichi; Shozen, Hideki; Adachi, Nobuo
Abstract: Background: We aimed to evaluate the associations between implant alignment/position and patient-reported outcomes following total hip arthroplasty using CT-based simulation software. Methods: We reviewed hips of 137 patients (27 males, 110 females, mean age: 67.3 years old) who underwent total hip arthroplasty. Radiographic evaluations were based on the software for evaluation of the parameters related to implant alignment/position and femoral/3-dimensional offset using post-operative CT data. Pre-operative and one-year post-operative patient-reported outcomes using Japanese Orthopaedic Association Hip Disease Evaluation Questionnaire scores were evaluated. Findings: The total and movement scores of normal combined anteversion and stem anteversion angle groups were significantly higher than those of lower and higher groups. The pain and movement scores of decreased femoral offset group were significantly lower than those of restored and increased femoral offset group. There were no significant differences in all scores in cup inclination and anteversion angle, stem coronal alignment, and 3-dimensional femoral offset among groups. Moreover, investigation of the associations between combined anteversion angle/stem anteversion/femoral offset and movement scores revealed that combined anteversion angle and stem anteversion were significantly associated with the movement that needs deep hip flexion and occasionally deep abduction, and high femoral offset was also associated with the movement that needs deep hip flexion. Interpretation: Surgeons should consider the stem anteversion, stem sagittal alignment, and combined anteversion, in addition to the femoral offset to achieve patient's post-operative satisfaction, although the surgeon may have a relatively larger choice for the implant positioning, especially on the cup side. Highlights: We evaluated the associations between implant settings and satisfaction in total hip arthroplasty. Stem anteversion and sagittal alignment were associated with post-operative satisfaction. Combined anteversion and femoral offset were also associated with post-operative patient's satisfaction. Cup position and alignment had no association with patient's post-operative satisfaction.